Hunger, Nutrition, Climate Justice - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The Dublin Conference on Hunger, Nutrition and Climate Justice aimed to facilitate dialogue between key policy makers and global thought leaders with local people and practitioners facing the realities of rising food prices, failed crops, undernutrition and voicelessness.